Measurement Invariance of Alabama Parenting Questionnaire Across Age, Gender, Clinical Status, and Informant. (April 2023) - Florean, Ionut Stelian; Dobrean, Anca; Balazsi, Robert; Roșan, Adrian; Păsărelu, Costina Ruxandra; Predescu, Elena; Rad, Florina
This study aimed to investigate the measurement invariance of the Alabama Parenting Questionnaire (for both long [APQ-lg] and short [APQ-9] forms) across age, gender, clinical status, and informant (i.e., parent vs. child reports). The sample was composed of adolescents (community sample: N = 1, 746; clinical sample: N = 166) and parents ( N = 149). The analyses were conducted in R. Measurement invariance was assessed via multi-group confirmatory factor analysis, equivalence test, and subsampling approach. The original model of APQ-lg (five factors) showed a significantly better fit than other concurrent models (five concurrent models were specified, based on prior literature). For APQ-lg, we found measurement invariance across gender and partial measurement invariance across age, clinical status, and informant. For APQ-9, we confirmed the measurement invariance across gender and clinical status, while across age and informant partial measurement invariance was attested. Overall, our study indicated that APQ-lg and APQ-9 are two valid tools for measuring parenting practices with some caveats.